The Qur'an and the Mapanre Teme Aqorang Tradition of the Bugis Ethnicity in East Kalimantan - Mursalim, Mursalim (Jurnal Adabiyah, 2023)
Reading the Qur'an is not only a ritual worship practice for the Bugis society, but the reading of the Qur'an is also linked to local rituals that have symbolic meanings and dimensions of very deep values amidst the plurality of Bugis society. The recitation of the Qur'an upon completion of Qur'anic studies is associated with a tradition known as 'mappanre temme aqorang'. This article aims to reveal the meaning of the ritual values of the Qur'an recitation tradition 'mappanre temme' as a local tradition of the Bugis community in the overseas country of Kalimantan. This tradition encompasses a belief system with forms and practices that can be traced to the present day. This phenomenological research uses a descriptive-qualitative approach and field-based data collection techniques by conducting in-depth interviews with the bearers of this tradition, namely the Bugis community in East Kalimantan and the religious leaders involved in the procession of this tradition. It was found that the traditional ritual of mappanre temme aqorang for the Bugis community is not just an ordinary ritual, but serves as a means of maintaining the identity of the Bugis community in the overseas country in the midst of a multicultural society in the Etam continent of East Kalimantan, both as a community that is highly religious and as a community that is loyal to ancestral traditions. In addition, the ritual serves as a glue for the Bugis' philosophical values of sipakatau, sipakalebbi and siamase-masei in social relations. Writings on Qur'anic studies and local wisdom in multicultural Indonesia have yet to be contextually and comprehensively explored as a cultural phenomenon. الملخص قراءة القرآن لمجتمع بوغيس ليست مجرد ممارسة عبادة طقسية ولكن قراءة القرآن مرتبطة أيضا بالطقوس المحلية التي لها معاني رمزية و قيم عميقة في تعددية مجتمع بوغيس. من أحد تقاليد قراءة القرآن هو تقليدختم القرآن “mappanre temme” بعد أن يكمل تعلم قراءة القرآن 30 جزءا. تهدف هذه المقالة إلى كشف معاني قيم الطقوس في تقليد قراءة القرآن المسمئ بـ"Mappanre Temme" أو ختم القرآن كتقليد محلي لمجتمع البوغيس في منطقة كاليمانتان في أواسط التعدد العرقي والثقافي في الحياة الاجتماعية والدينية. يحتوي هذا التقليد على معتقدات ذات أشكال وممارسات لم تزل تتمكن مصافحتها حتى اليوم. يستخدم هذا البحث الظاهري منهجًا وصفيًا نوعيًا وتقنيات جمع البيانات الميدانية من خلال إجراء مقابلات متعمقة مع فاعلي هذا التقليد، أي مجتمع بوغيس في كاليمانتان الشرقية والأساتذة / ورجال الدين المشاركين في هذا التقليد. لقد وجد أن طقوس ختم القرآن "Mappanre Temme Akorang" التقليدية لمجتمع البوغيس ليست مجرد طقوس عادية ولكنها تنفّذ كوسيلة للمحفاظة على هوية مجتمع البوغيس الأراضي البعيدة وسط مجتمع متعدد الثقافات في قارة إيتام في شرق كاليمانتان، سواء كمجتمع مطيع في ممارسة دينه أو ولاءه لتقاليد الأجداد. بالإضافة إلى ذلك، فإن هذه الطقوس تعد وسيلة لربط قيم فلسفة شعب بوغيس، وهي تبادل الإحترام sipakatau، وتبادل المجد sipakalebbi، وتبادل الحب siamase-masei، بالعلاقات الاجتماعية في المجتمع. كانت الكتابة حول دراسات القرآن والحكمة المحلية في إندونيسيا مع المجتمعات المتعددة الثقافات إلى استكشاف سياقي وشامل كظاهرة ثقافية. عرق بوغيسى, Maccera Aqorang، الكلمات المفتاحية: تقليد محلى, حتم القرآن Abstrak Artikel ini ingin mengungkap makna nilai-nilai ritual tradisi pembacaan al-Qur’an “mappanre temme” sebagai tradisi lokal masyarakat Bugis di tanah rantau Kalimantan di tengah pluralitas etnis dan budaya dalam kehidupan sosial-keagamaan. Tradisi ini mengandung sebuah keyakinan dengan bentuk dan praktek yang masih bisa ditelusuri hingga saat ini. Penelitian fenomenologi ini dengan pendekatan deskriptif-kualitatif dan teknik pengumpulan data berbasis lapangan dengan melakukan wawancara mendalam kepada pelaku tradisi ini, yaitu masyarakat Bugis yang berada di Kaltim dan para ustaz/tokoh agama yang terlibat dalam prosesi tradisi ini. Ditemukan bahwa ritual tradisi mappanre temme aqorang bagi masyarakat Bugis bukan sekedar sebuah ritual biasa tetapi berfungsi sebagai sarana untuk mempertahankan identitas masyarakat Bugis di tanah rantauan di tengah masyarakat yang multikultural di Benua Etam Kaltim, baik sebagai masyarakat yang sangat taat menjalankan agama maupun kesetiaannya terhadap tradisi leluhur. Di samping itu, ritual ini menjadi perekat terhadap nilai falsafah orang Bugis, yaitu sipakatau, sipakalebbi, dan siamase-masei terhadap hubungan sosial-masyarakat. Tulisan tentang studi kajian Al-Qur’an dan kearifan lokal di Indonesia yang multikultural, masih perlu dieksplorasi secara kontekstual dan komprehensif sebagai fenomena budaya. Kata Kunci: Tradisi lokal; Mappanre Temme Aqorang; Maccera Aqorang; Etnis Bugis